2014
DOI: 10.1002/2013jd021297
|View full text |Cite
|
Sign up to set email alerts
|

Net terrestrial CO2exchange over China during 2001-2010 estimated with an ensemble data assimilation system for atmospheric CO2

Abstract: In this paper we present an estimate of net ecosystem CO 2 exchange over China for the years 2001-2010 using the CarbonTracker Data Assimilation System for CO 2 (CTDAS). Additional Chinese and Asian CO 2 observations are used in CTDAS to improve our estimate. We found that the combined terrestrial ecosystems in China absorbed about À0.33 Pg C yr À1 during 2001-2010. The uncertainty on Chinese terrestrial carbon exchange estimates as derived from a set of sensitivity experiments suggests a range of À0.29 to À0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 78 publications
(156 reference statements)
2
44
2
Order By: Relevance
“…And our estimate was significantly higher than that during 1981-2000 based on a variety of ways [25], and was also higher than the sink during 2001-2010 (0.28-0.33 PgC a -1 , Table 8) obtained from atmospheric inversion method [24,83], models [79] and resource inventory method [84,85]. These differences resulted primarily for two reasons.…”
Section: Uncertainty In the Assessment Of Carbon Sinkcontrasting
confidence: 57%
See 1 more Smart Citation
“…And our estimate was significantly higher than that during 1981-2000 based on a variety of ways [25], and was also higher than the sink during 2001-2010 (0.28-0.33 PgC a -1 , Table 8) obtained from atmospheric inversion method [24,83], models [79] and resource inventory method [84,85]. These differences resulted primarily for two reasons.…”
Section: Uncertainty In the Assessment Of Carbon Sinkcontrasting
confidence: 57%
“…Currently, the methods used in the determination of ecosystem productivity and the evaluations of the carbon budget at different spatial and temporal scales include eddy covariance [11], resource inventory [12,13], airborne laser scanning [14], remote sensing evaluation based on resource satellite observations [15], remote sensing inversion of carbon satellites [16,17], geographical statistical modeling [18,19], analysis based on process-based models [20][21][22] and atmospheric inversion [23,24]. These technologies have improved continually with their own appropriate spatiotemporal scales, and researchers have also performed meta-analyses based on multi-source data from different approaches [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Retrievals of XCO 2 from the near-infrared nadir spectral radiance and solar irradiance measurements of the SCIAMACHY satellite instrument between 2003 and 2005 are compared with global XCO 2 obtained from CarbonTracker, which showed that the measured CO 2 year-toyear increase agrees within about 1 ppm/year with CarbonTracker (Buchwitz et al 2006). The Carbon Tracker was used to estimate net ecosystem CO 2 exchange over China for the period from 2001 to 2010, in which additional Chinese and Asian CO 2 observations were input to improve its estimation accuracy (Zhang et al 2014a). Carbon Tracker was also applied to estimate the carbon flux of Asia by combining CO 2 data from the Comprehensive Observation Network for Trace gases by Airline (CONTRAIL) with ground CO 2 observations distributed by NOAA-ESRL and the World Data Centre for Greenhouse Gases (WDCGG) (Zhang et al 2014b).…”
Section: Classical Methodsmentioning
confidence: 99%
“…More broadly, evaluation against all types of independent atmospheric observations provides an additional window into the degree to which estimated fluxes capture key features of the atmospheric signal, such as the seasonal cycle, latitudinal gradients, or regional patterns of concentrations (e.g., Zhang et al, 2014;Jiang et al, 2014;Díaz Isaac et al, 2014;Pandey et al, 2016;Liu and Bowman, 2016;Johnson et al, 2016).…”
Section: Evaluation Against Unused Atmospheric Observationsmentioning
confidence: 99%